Artisans/Appalachia/USA - Gaynes, David (Appalachian State University, 2021)
This is the documentation of an Appalachian Consortium traveling exhibition of Appalachian Art produced in the 1970s. The project was supported by a grant from the National Endowment for the Arts in Washington, D.C.